A goat eye, wet lab model for training in Descemet membrane endothelial keratoplasty - Nidhi Gupta; Maninder Bhogal; Pravin K Vaddavalli; Alessandro Boldini; Francesco Semeraro; Akhil Varshney; Vito Romano (Indian Journal of Ophthalmology, 2023)
Here we describe a new, non-human, ex-vivo model (goat eye model) for training surgeons in DMEK surgeons. In a wet lab setting, goat eyes were used to obtain a pseudo-DMEK graft of 8 mm from the goat lens capsule that was injected into another goat eye with the same maneuvers described for human DMEK. The DMEK pseudo-graft can be easily prepared, stained, loaded, injected, and unfolded into the goat eye model reproducing the similar maneuvers used for DMEK in a human eye, except for the descemetorhexis, which cannot be performed. The pseudo-DMEK graft behaves similar to human DMEK graft and useful for surgeons to experience and understand steps of DMEK early in learning curve. The concept of a non-human ex-vivo eye model is simple and reproducible and obviates the need for human tissue and the issues of poor visibility in stored corneal tissue.